2016
DOI: 10.1038/srep25543
|View full text |Cite|
|
Sign up to set email alerts
|

Evolved resistance to colistin and its loss due to genetic reversion in Pseudomonas aeruginosa

Abstract: The increased reliance on colistin for treating multidrug-resistant Gram-negative bacterial infections has resulted in the emergence of colistin-resistant Pseudomonas aeruginosa. We attempted to identify genetic contributors to colistin resistance in vitro evolved isogenic colistin-resistant and -susceptible strains of two P. aeruginosa lineages (P5 and P155). Their evolutionary paths to acquisition and loss of colistin resistance were also tracked. Comparative genomic analysis revealed 13 and five colistin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 58 publications
3
57
1
4
Order By: Relevance
“…2)283940. This specific phoQ mutation has also been identified in clinical and in vitro evolved isolates with increased col R (refs 30, 38, 41). These findings argue against inactivation of a negative regulator as an adequate explanation for the selective preference of this specific mutation.…”
Section: Discussionmentioning
confidence: 85%
“…2)283940. This specific phoQ mutation has also been identified in clinical and in vitro evolved isolates with increased col R (refs 30, 38, 41). These findings argue against inactivation of a negative regulator as an adequate explanation for the selective preference of this specific mutation.…”
Section: Discussionmentioning
confidence: 85%
“…One reason why colistin-resistant strains do not emerge as frequently in clinical settings as in in vitro experiments could be fitness costs and impaired virulence associated with resistance. Lee et al (11) observed rapid reversion of colistin resistance mutations in P. aeruginosa. Similarly, references 47 and 48 describe fitness costs of colistin resistance in Acinetobacter baumannii isolates, while others also reported an inhibited growth of colistinresistant LPS mutants in fetal bovine serum (49) and a decreased production of capsular polysaccharides in a Klebsiella pneumoniae strain (50).…”
Section: Discussionmentioning
confidence: 99%
“…These mutations alter the outer membrane of P. aeruginosa by addition of 4-amino-4-deoxy-L-arabinose (L-Ara4N) to phosphate groups of the LPS lipid A region. The resulting reduced negative charge decreases the uptake of polycationic antimicrobial peptides and lipopeptide polymyxins (11). This modification is typically induced by enzymes that are encoded in the arnBCADTEF-PA3559 (PA3552-PA3559) operon (12).…”
mentioning
confidence: 99%
“…A better understanding of the molecular mechanisms responsible for the reduced colistin susceptibility in the subpopulations of each strain with higher colistin MICs is now of great interest to better understand the mechanism of synergy observed with CHIR-090. Inactivation of lipid A biosynthesis has already been reported to be associated with reduced susceptibility to colistin in Acinetobacter baumannii and recently in P. aeruginosa (20,21) Of interest, a complex and reversible mechanism involving the regulatory network, genetic alterations, and lipid A biosynthesis was suggested in P. aeruginosa (22). These findings highlight the great interest in inhibitors of lipid A biosynthesis and their therapeutic potential in combination with colistin for the treatment of Gram-negative bacterial infections associated or not associated with biofilms.…”
Section: Figmentioning
confidence: 99%